2017
DOI: 10.1007/s11010-017-3185-8
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic renal cells induce lymphocytosis of Th22 cells from IgA nephropathy patients through B7–CTLA-4 and CCL-CCR pathways

Abstract: IgA nephropathy (IgAN), the most common glomerulonephritis, has an unclear pathogenesis. The role of Th22 cells, which are intimately related to proteinuria and progression in IgAN, in mediating infection-related IgAN is unclear. This study aimed to characterize the association between intrinsic renal cells (tubular epithelial cells and mesangial cells) and Th22 cells in immune regulation of infection-related IgAN and to elucidate the impact of Th22 lymphocytosis; the proinflammatory cytokines IL-1, IL-6, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Moreover, elevation of Th22 cells in patients’ peripheral blood was associated with worse histologic renal images; the percentage of Th22 cells was positively correlated with MEST scores. Authors concluded that tonsillitis aggravated renal injury in IgAN through induction of Th22 lymphocytosis, infiltration of renal tissue, and promotion of renal fibrosis by Th22 [16, 76].…”
Section: Renal Injury—th2 Th17 Th22 and Treg Cells Participation Inmentioning
confidence: 99%
“…Moreover, elevation of Th22 cells in patients’ peripheral blood was associated with worse histologic renal images; the percentage of Th22 cells was positively correlated with MEST scores. Authors concluded that tonsillitis aggravated renal injury in IgAN through induction of Th22 lymphocytosis, infiltration of renal tissue, and promotion of renal fibrosis by Th22 [16, 76].…”
Section: Renal Injury—th2 Th17 Th22 and Treg Cells Participation Inmentioning
confidence: 99%
“…4,5 However, IgAN was considered as one complex multifactorial disease, immunology and genetics mechanisms were proved to play critical roles in the development and pathogenesis of IgAN. [6][7][8] Growing evidences suggested that B lymphocytes were increased in cases with high concentration of the IgA in the serum. 6,9 IgA1 in the serum is abnormally O-glycosylated, which causes IgA1 mesangial deposition and glomerular injury developing into IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…IL-22 is mainly secreted by lymphoid cells such as Th22, Th17, NKT and innate lymphoid cells (ILCs) [32], Th22. Recent studies have reported the reno-protective effects of IL-22 in acute kidney injury and CKD [20,21], however we and other groups verified that Th22 and IL-22 promoted renal damage in IgA nephropathy and hypertension [33][34][35][36]. Whether IL-22 is protective or destructive in kidney diseases may depend on different microenvironment.…”
Section: Discussionmentioning
confidence: 68%